PERUBAHAN BUDAYAORGANISASI DAN PENGARUHNYATERHADAPKINERJAKARYAWAN : SUATU TINJAUAN PUSTAKA - Andarias Patiran (STIE Pelita Nusantara Semarang, 2007)
The aim of this written article is to know and explain the conceptual work plan of the organization culture to the employees service in a organization.The culture change which happens in a organization flows and appears in a movement, conflic, or bump, but its not a frightened thing.A change is needed, even in a little scale. It shows that there is a life in an organization, if the change is managed well and consistently by regarding the man power will product the development and increase the employees service in a organization